Implementation of P5 in Instilling Democratic Values through the Election of Student Council Chairperson - Yamani, Muhamad Zaky; Habibi, Beni; Maufur, Maufur (Journal of English Language and Education, 2025)
Instilling democratic values in students at school is an important part of character building for the young generation who have a sense of nation and state. One effort that can be made is to implement a program to strengthen the profile of Pancasila Students through the election of the OSIS Chairperson at SMA Nahdlatul Ulama, Tegal City. The election of the OSIS chairperson is not only an event to elect student leaders, but also a medium for instilling democratic values, which is an important aspect of the Pancasila Student profile. This study aims to analyze how the implementation of the Pancasila Student profile strengthening project can be carried out in the context of the election of the OSIS chairperson at SMA Nahdlatul Ulama, Tegal City. This study uses a descriptive qualitative approach with a case study method to identify the application of democratic values in the OSIS chairperson election process. The results of the study show that the OSIS chairperson election process at SMA Nahdlatul Ulama, Tegal City has succeeded in integrating democratic values in each stage. Students can find out about the process of the Pancasila student profile strengthening project in instilling democratic values through the election of the OSIS chairperson. Participants can understand and actively participate in each stage. This provides real experience for students in implementing healthy and just democratic values.